2005
DOI: 10.1016/j.amjhyper.2004.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fish oil prevents vascular dysfunction and oxidative stress in hyperinsulinemic rats

Abstract: These results demonstrate that dietary fish oil prevents vascular dysfunction in FFR and that this effect of fish oil is associated with increased eNOS expression and decreased oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 38 publications
4
22
2
Order By: Relevance
“…Therefore, as a potential AD-relevant model, we chose insulin-resistant rats on a high fructose corn syrup diet. Dietary fish oil has been reported to prevent oxidative stress in this model (Nyby et al, 2005). We observed that supplementation with 2.2% fish oil diet containing 0.24% DHA and 0.36% EPA for 8 weeks, significantly increased LR11 protein levels in 3-to 4-month-old insulin resistant rats compared with the control fructose-fed group (**p Ͻ 0.01).…”
Section: Dha Increases Lr11 Protein Levels In Human Neural Sh-sy5y Cesupporting
confidence: 51%
“…Therefore, as a potential AD-relevant model, we chose insulin-resistant rats on a high fructose corn syrup diet. Dietary fish oil has been reported to prevent oxidative stress in this model (Nyby et al, 2005). We observed that supplementation with 2.2% fish oil diet containing 0.24% DHA and 0.36% EPA for 8 weeks, significantly increased LR11 protein levels in 3-to 4-month-old insulin resistant rats compared with the control fructose-fed group (**p Ͻ 0.01).…”
Section: Dha Increases Lr11 Protein Levels In Human Neural Sh-sy5y Cesupporting
confidence: 51%
“…Diets high in fish oils prevent hyperinsulinemia, hypertriglyceridemia, and hypertension in fructose-and dexamethasone-induced hypertensive rat models [184][185][186]. Increased PUFA intake is associated with a reduction of reactive oxygen species and an increase in antioxidants during hypertension [187][188][189]. Dietary fish oils can prevent LVH in transgenic mice with a carnitine transporter mutation, which was attributed to modified diacylglycerol composition and resultant inhibition of PKC activation [190].…”
Section: Polyunsaturated Fats and Fish Oilsmentioning
confidence: 97%
“…The CONT+CAP and FFR +CAP were thereafter given drinking water containing 500 mg/L captopril (ICN Chemicals, Costa Mesa, USA). Systolic blood pressure was measured weekly using a tail-cuff method with an optical sensor (IITC, Woodland Hills, USA) as previously described (2,13). Measures were taken to reduce stress in the rats while their blood pressures were determined.…”
Section: Animalsmentioning
confidence: 99%
“…Feeding normal rats a high-fructose diet induces insulin resistance, hypertension, dyslipidemia and vascular dysfunction (1,2). Although the fructose-fed rat (FFR) model exhibits many metabolic disorders, the cause of hypertension in these animals is not known.…”
Section: Introductionmentioning
confidence: 99%